Structure-properties relationship of chitosan/collagen films with potential for biomedical applications. (1st June 2020) - Andonegi, Mireia; Heras, Kevin Las; Santos-Vizcaíno, Edorta; Igartua, Manoli; Hernandez, Rosa Maria; de la Caba, Koro; Guerrero, Pedro
Highlights: Chitosan addition preserved the triple-helix structure of native collagen. There was no need to add chemical crosslinkers into chitosan/collagen formulations. Chitosan/collagen films showed a suitable water vapor transmission rate for wound dressings. Biological tests suggest that chitosan can be used to control the film degradation rate. Cell viability was higher than 70 % for chitosan/collagen films. Abstract: Chitosan/collagen films were developed and characterized in order to assess the suitability of these films for biomedical applications. Hence, physicochemical, thermal, barrier and mechanical properties were analyzed and related to the film structure, which showed the prevalence of the triple helix of native collagen after the addition of chitosan. Furthermore, collagen fiber diameter changed from 3.9 ± 0.6 μm, for collagen films without chitosan, to 1.8 ± 0.5 μm, for collagen films with low molecular weight chitosan. These results suggested interactions between collagen and chitosan molecules, as observed by Fourier transform infrared (FTIR) analysis. Regarding film barrier properties, chitosan/collagen films showed a water vapor transmission rate around 1174 g m −2  day −1, suitable for biomedical applications such as wound healing. Additionally, biological tests confirmed that the chitosan/collagen films developed are suitable for biomedical applications.